Edificio Nativo Wayuu. (2022)
The interest in studying Wayuu vernacular architecture arises from the need to recognize the ancestral and traditional architectural values ​​of this culture, as well as the compositional values ​​understood as the unity and relationship between the place and the building. It should be noted that there is a very important constant cultural uprooting in our country by modern society, due to its way of understanding the cultural and architectural traditions of indigenous communities; which still preserve their ancestral traditions and try to maintain them over the cultures that constantly invade them, spreading throughout the Colombian territory accompanied by great challenges in terms of quality of life.